Model Pembelajaran CTL Berbantuan Media Pop-Up Book untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa SD - Anis Zulfatin Nihayah; Fina Fakhriyah; Much Arsyad Fardhani (Universitas Pendidikan Indonesia Kampus Serang, 2019)
Creative thinking belongs to high-order thinking. It is important to see various possible solutions to a problem. Students with various possibilities of solving a problem will be more creative. It is necessary to foster the creative thinking skill since elemenetary school level. This research has intended to find out the improvement of the students’ creative thinking by using the model of contextual teaching and learning assisted by pop-up book media. This research is conducted in fifth grade of elementary school with 26 students. The researcher used classroom action research method in 2 cycles. Each cycle consisted of planning, implementation, observation, and reflection. Data collection techniques that the researcher used are interview, observation, pre-test, and documentation. The researchers used quantitative and qualitative data analysis. The result of this research show that there is improvement of student’ creative-thinking on 6th theme “Heat and Its Displacement” from 54% in the cycle 1 then improve to be 85% in the cycle 2. So, from this research the researchers can conclude that the model of contextual teaching and learning assisted by pop-up book media can improve elementary school students’ creative thinking skill.